Determining the Importance of SOP in a Family Business from the Entrepreneurial Perspective - Hongdiyanto, Charly; Hartono, Wendra; Ongkowijoyo, Gracia (Modern Perspectives in Economics, Business and Management Vol. 5, 2021)
Plastic industry is a growing sector, therefore UD X which engage in this business has a great potential to grow as well. The problem faced by this family business company is that no standard operating procedure is used and it lead to problem in the quality and quantity produced, which from an entrepreneurial point of view, this is very important. This research is aim to create a production standard operating procedure for UD X, thus, this family business can carry out company activities properly. Semi-structure interview is used to gather information from respondent to help writer create the SOP. There are four SOP’s created, namely: classifying SOP, sorting SOP, milling SOP and packing SOP.